Complex atrial arrhythmias as first manifestation of catecholaminergic polymorphic ventricular tachycardia: an unusual course in a patient with a new mutation in ryanodine receptor type 2 gene. (28th August 2013) - Lawrenz, Wolfgang; Krogmann, Otto N.; Wieczorek, Marcus
Abstract Catecholaminergic polymorphic ventricular tachycardia is a rare life-threatening arrhythmogenic disorder. An association with paroxysmal atrial fibrillation and other atrial arrhythmias has been described, but in all published cases the initial manifestation of the disease was ventricular arrhythmia. This is the first report about a patient who presented with complex atrial tachycardia and sinus node dysfunction about 1 year before the typical ventricular arrhythmias were observed, leading to the diagnosis of catecholaminergic polymorphic ventricular tachycardia. In this girl, a mutation of the ryanodine receptor type 2 gene, which has not been described so far, was discovered.